Correlation Between Anterior Chamber Volume and Corneal Biomechanical Properties in Human Eyes - Cui, Xinhan; Yang, Yujing; Li, Yue; Huang, Feifei; Zhao, Yujin; Chen, Huiyu; Xu, Jianjiang; Mashaghi, Alireza; Hong, Jiaxu (Frontiers in Bioengineering and Biotechnology, 2019)
Purpose: To investigate the correlation between anterior chamber volume (ACV) and corneal biomechanical properties in healthy and primary angle closure (PAC) eyes. Methods: A total of 79 eyes from 55 participants were enrolled in this study, including 24 eyes from 17 PAC patients and 55 eyes from 38 normal subjects. Anterior chamber volume was detected via swept-source anterior segment optical coherence tomography (OCT), and the cornea biomechanical data were obtained via corneal visualization Scheimpflug technology (Corvis ST). A student’s t-test, Chi-square test, Pearson’s correlation coefficients, and linear regression were used in the statistical analysis. Results: Anterior chamber volume was significantly associated with a lower deformation altitude (DA) (p = 0.033), higher stiffness parameter (SP-A1) (p = 0.005), younger age (p = 0.001), and higher biomechanical intraocular pressure (bIOP) (p = 0.001). PAC patients were suspected to have a much shallower anterior chamber than healthy participants. In the PAC group, the mean ACV (p < 0.01), SP-A1 (p < 0.01), and bIOP values (p = 0.01) were significantly reduced as compared to the normal group, and DA values (p = 0.02) and age (p = 0.01) were increased as compared to the normal group. Conclusions: Bigger ACV was associated with lower DA values and age, as well as higher SP-A1 and bIOP values. Reduced corneal stiffness was more commonly found in the PAC suspects as compared to their normal counterparts, indicating a protective physiological mechanism for people with shallower anterior chambers that protects against potential elevations of IOP.